1982
DOI: 10.1007/bf01570638
|View full text |Cite
|
Sign up to set email alerts
|

Use of radio-frequency pulsed energy in the control of postoperative reaction in blepharoplasty

Abstract: This is a preliminary report of the use of a device to apply small pulses of radio-frequency energy to surgical wounds in order to improve wound healing. The device was applied to one eye in 21 patients who underwent bilateral blepharoplasty. There were no device-related complications. In 11 patients, edema and ecchymosis were noticeably less on the treated side within 24 hours of surgery. In 6 patients, ecchymosis and swelling were so slight that no difference between treated and untreated sides was visible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The control condition was a 15-W light bulb. Applying this concept to postoperative recovery, Nicolle and Bentall [10] demonstrated the control of edema and bruising during postoperative recovery from blepharoplasty using a low-energy, extended-use PRFE device.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The control condition was a 15-W light bulb. Applying this concept to postoperative recovery, Nicolle and Bentall [10] demonstrated the control of edema and bruising during postoperative recovery from blepharoplasty using a low-energy, extended-use PRFE device.…”
Section: Discussionmentioning
confidence: 97%
“…Some of the first studies investigating postoperative edema and edema caused by soft tissue injury showed promising results [9,10]. Studies on postoperative pain also showed good results [11][12][13].…”
mentioning
confidence: 99%
“…[6][7][8][10][11][12][13]15,17,19,20,[23][24][25] Of the 14 controlled studies, 8 were randomized controlled trials (3 PO and 5 NPO) and 7 were blinded studies (2 PO and 5 NPO). Eleven of the 14 controlled clinical trials were evaluable for the P-value combination analysis (3 PO and 8 NPO).…”
Section: Edemamentioning
confidence: 99%
“…50 The literature also suggests that PSWD is replacing short-wave diathermy and the emphasis should be on the efficacy of PSWD. [51][52][53] No studies relating to this form of electrotherapy were retrieved, but this format could be the basis of a controlled trial in the future.…”
Section: Discussionmentioning
confidence: 99%